Entre as exigências de tempo e os constrangimentos do espaço : as condições acidentogênicas e as estratégias de regulação dos motociclistas profissionais - Eugênio Paceli Hatem Diniz (2003)
The investigative focus of this study is on the services provided by professional motorcyclists, and it is aimed at meeting the demands that have been formulated by the workers’ union, as well as revealing elements that can support the social actors in negotiations regarding the improvement of working conditions for this specific class. In order to do so, this work attempted to unveil the activities of professional motorcyclists and the way in which work relations and organization reflect upon the strategies and the operational method implemented by this class. In order to achieve an understanding of this activity, Ergonomics was adopted as research methodology, along with its method of action – Ergonomic Analysis of Labour. Empirical data were obtained from observation and filming in traffic, from one company in Belo Horizonte/MG, and another in Uberlândia/MG. Eighty-five professional motorcyclists were interviewed and their activities were observed and self-confronted. We also carried out a study and self-confrontation of the routes elaborated on maps by twenty-four professional motorcyclists. Results revealed that organization and work relations in the companies that provide professional motorcyclist services are determined by the new inter-enterprise relations. Clients demand punctual, prompt and reliable service, and do not take into account that material and non-material activities cannot be dissociated. In fact, professional motorcyclists are submitted to intense service demands and time pressure. In order to satisfy their clients’ time-related demands and deal with the space constraints, professional motorcyclists find in the work collective and in route and time planning the solution that meets production demands and guarantees their survival. Several strategies and operational methods have been developed and put into effect by these workers in offices, in the traffic, with clients and in the researched companies. The analysis of the activities showed the motorcyclists from a productive perspective, as workers concerned with guaranteeing a commitment between production and safety. This made it possible to elaborate twenty-five suggestions so that the social actors involved in the Health & Labour process could initiate negotiations. It is hoped that these suggestions, once implemented, will reduce morbimortality rates and reverse the stigmatizing perception that society holds regarding this class of workers.